Concerning Nuisances Not in Streets, The Charter and Ordinances of the City of Richmond, Title 7, Ch. 46, §12 (1869). - (:unkn) unknown (My University, 1869)
No person, firm or incorporated company shall keep in any house in the city any loaded shell or shot, or any explosive material of any sort, not authorized by ordinance. And any person, firm or incorporated company violating the provisions of this section shall be fined not less than twenty nor more than one hundred dollars; and each day on which the same is so kept in the city shall be a distinct offence and punishable as such."
Keywords: GUNPOWDER - STORAGE